Reconstructing Environmental Ethics Through FGD: A Case Study of River Conservation and Local Myths Demystification in Pakis Kembar - Anggun Trisnanto Hari Susilo (PT Keberlanjutan Strategis Indonesia, 2026)
This study examines the reconstruction of environmental ethics in Pakis Kembar Village through Focus Group Discussion (FGD) within the frameworkParticipatory Action Research (PAR). The background of the study focuses on the high level of domestic waste accumulation and the practice of dumping waste into rivers influenced by local myths, namely throwing baby diapers into rivers. This study conducted an FGD on November 5, 2025, using a PAR approach involving local governments, religious leaders, local communities, academics, practitioners, and the private sector to explore the roots of socio-cultural problems and formulate community-based solutions. The results of the study indicate that waste management problems are not only caused by limited infrastructure, but also by mental models and local knowledge systems.(indigenous knowledge system). Through inter-epistemological dialogue, FGD effectively facilitates the process of demystifying local myths, building collective awareness, identifying local champions, and producing the compilation master plan eco edu tourism, a river conservation roadmap that integrates environmental education, value change, and technical interventions. However, the implementation of this initiative still faces challenges, such as the need for long-term mentoring, strengthening women's representation, and implementing technical ideas into real-world practice. Based on these results, this study recommends strategies value-based intervention, integration of practice-based environmental education, and strengthening cross-regional networks to support upstream and downstream conservation.